Association Between Interoception and Emotion Regulation in Individuals With Alcohol Use Disorder - Jakubczyk, Andrzej; Trucco, Elisa M.; Klimkiewicz, Anna; Skrzeszewski, Jakub; Suszek, Hubert; Zaorska, Justyna; Nowakowska, Malwina; Michalska, Aneta; Wojnar, Marcin; Kopera, Maciej (Frontiers in Psychiatry, 2020)
Introduction: Sensing body-related information includes interoceptive sensibility (the tendency to focus on internal body sensations) and accuracy (precision in perceiving real internal processes). Interoception and emotion regulation have both been linked to alcohol use disorder (AUD). However, the association between these factors have not been investigated within a clinical group of individuals with AUD. Objectives: The current study examines associations between emotion regulation and interoceptive accuracy and sensibility among individuals with AUD and healthy controls (HCs). Methods: The sample comprised 165 individuals meeting criteria for AUD and 110 HCs. Interoceptive sensibility was assessed with a self-report measure (the Private Body Consciousness subscale) and interoceptive accuracy – with a behavioral measure (the Schandry test). Emotion regulation domains: non-acceptance of negative emotions, inability to engage in goal-directed behaviors when experiencing negative emotions, difficulties controlling impulsive behaviors when experiencing negative emotions, limited access to effective emotion regulation strategies, and lack of own emotional awareness and clarity were assessed with the Difficulties in Emotion Regulation Scale (DERS). Associations between interoception and emotion regulation were assessed while controlling for sleep problems, depressive symptoms, age, and sex. Results: Higher interoceptive accuracy was negatively associated with DERS subscale of non-acceptance of negative emotions in the AUD group (but not in the HC group). Higher interoceptive sensibility was significantly associated with problems in controlling impulsive behaviors when experiencing negative emotions. This association was moderated by symptoms of AUD. Higher interoceptive sensibility was associated with higher emotional awareness, but only in the HC group. Conclusions: Individuals with AUD who are more interoceptively accurate may be more effective in regulating their emotions. On the other hand, individuals with AUD who are more interoceptively sensible, may have problems with controlling their behaviors while experiencing negative emotional states.